Long-term follow-up of a multimodal day clinic, group-based treatment program for patients with very high risk for complex posttraumatic stress disorder, and for patients with non-complex trauma-related disorders - Bever-Philipps, Anke; Silbermann, Andrea; Morawa, Eva; Schäflein, Eva; Stemmler, Mark; Erim, Yesim (Frontiers in Psychiatry, 2023)
Objective The present study examined the follow-up of a multimodal day clinic group-based therapy program for patients with trauma-related disorders and investigated potential differences for patients with classic PTSD versus cPTSD. Method Sixty-six patients were contacted 6 and 12 months after discharge of our 8-week program and completed various questionnaires (Essen Trauma Inventory (ETI), Beck Depression Inventory-Revised (BDI-II), Screening scale of complex PTSD (SkPTBS), Patient Health Questionnaire (PHQ)-Somatization, as well as single items to therapy utilization and life events in the interim period). Due to organizational reasons a control group could not be included. Statistical analyses included repeated-measures ANOVA with cPTSD as between-subject factor. Results The reduction of depressive symptoms at discharge was persistent at 6 and 12 months follow-up. Somatization symptoms were increased at discharge, but were leveled out at 6 months follow-up. The same effect was found for cPTSD symptoms in those patients with non-complex trauma-related disorders: Their increase of cPTSD symptoms was flattened at 6 months follow-up. Patients with a very high risk for cPTSD showed a strong linear reduction of cPTSD symptoms from admission to discharge and 6 months follow-up. cPTSD patients had a higher symptom load compared to patients without cPTSD on all time points and scales. Conclusion Multimodal, day clinic trauma-focused treatment is associated with positive changes even after 6 and 12 months. Positive therapy outcomes (reduced depression, reduced cPTSD symptoms for patients with a very high risk for cPTSD) could be maintained. However, PTSD symptomatology was not significantly reduced. Increases in somatoform symptoms were leveled out and can therefore be regarded as side effects of treatment, which may be connected with actualization of trauma in the intensive psychotherapeutic treatment. Further analyses should be applied in larger samples and a control group.